Conserved and Plant-Unique Mechanisms Regulating Plant Post-Golgi Traffic - Fujimoto, Masaru; Ueda, Takashi (Frontiers in Plant Science, 2012)
Membrane traffic plays crucial roles in diverse aspects of cellular and organelle functions in eukaryotic cells. Molecular machineries regulating each step of membrane traffic including the formation, tethering, and fusion of membrane carriers are largely conserved among various organisms, which suggests that the framework of membrane traffic is commonly shared among eukaryotic lineages. However, in addition to the common components, each organism has also acquired lineage-specific regulatory molecules that may be associated with the lineage-specific diversification of membrane trafficking events. In plants, comparative genomic analyses also indicate that some key machineries of membrane traffic are significantly and specifically diversified. In this review, we summarize recent progress regarding plant-unique regulatory mechanisms for membrane traffic, with a special focus on vesicle formation and fusion components in the post-Golgi trafficking pathway.